ANALISIS PEMAHAMAN MENGHITUNG PERKALIAN DENGAN MEDIA BENDA-BENDA TERDEKAT PADA SISWA KELAS IV SDN 143 PALEMBANG - Ida Suryani; Jayanti; Anggun Pratika (STKIP Subang, 2023)
ABSTRAC Mathematics is one of the compulsory subjects in elementary school. Students are required to have four basic mathematical competencies, one of which is multiplication. This study aims to identify students' understanding of concepts in understanding multiplication arithmetic operations and the difficulties experienced by students in completing multiplication arithmetic operations as well as the factors that influence these difficulties to occur. This type of research is qualitative research using descriptive methods. This research was conducted at Elementary School 143 Palembang in May 2023 with the research subjects namely 23 grade IV students at Elementary School 143 Palembang. The instruments in this study were tests, interviews and documentation. The data analysis technique used is the interactive model data analysis. Analysis Miles And Huberman consisting of data reduction, data presentation and drawing conclusions. The results showed that 13 students were included in the Incomplete category in the multiplication concept and 10 students were included in the Complete category in the multiplication concept. Difficulties experienced by students in multiplied numbers; difficulty understanding sentences in word problems; difficulties in determining how to solve math problems related to everyday problems often forget the basic multiplication that has been memorized; cannot change the multiplication form into repeated addition form; unable to determine known sentences and sentences asked in story problems; cannot solve multiplication arithmetic operation problems independently because they still need the help of others. Factors that influence the difficulties experienced by students namely; do not understand the concept of multiplication; using the memorized method in learning multiplication arithmetic operations. Keywords: Understanding the Multiplication Concept, arithmetic operations ABSTRAK Matematika merupakan salah satu mata pelajaran wajib diSekolah Dasar. Siswa dituntut untuk memiliki empat kompetensi dasar matematika salah satunya adalah perkalian. Penelitian ini bertujuan untuk mengidentifikasi pemahaman konsep pada siswa dalam memahami operasi hitung perkalian dan kesulitan yang dialami siswa dalam menyelesaikan operasi hitung perkalian serta faktor-faktor yang mempengaruhi kesulitan itu terjadi. Jenis penelitian ini adalah penelitian kualitatif dengan menggunakan metode Deskritif. Penelitian ini dilaksanakan di Sekolah Dasar 143 Palembang pada bulan Mei 2023 dengan subjek penelitian yaitu 23 siswa kelas IV Sekolah Dasar 143 Palembang. Instrument dalam penelitian ini adalah tes, wawancara dan dokumentasi. Teknik analisis data yang digunakan yaitu analisis data model Interaktif. Analysis Miles And Huberman yang terdiri dari reduksi data, penyajian data dan penarikan kesimpulan.Hasil penelitian menunjukkan bahwa 13 siswa termasuk kategori Tidak Tuntas dalam konsep perkalian dan 10 siswa termasuk kategori Tuntas dalam konsep perkalian. Kesulitan yang dialami siswa dalam bilangan yang dikalikan; kesulitan memahami kalimat pada soal cerita; kesulitan menentukkan cara dalam menyelesaikan masalah matematika yang berhubungan dengan masalah sehari-hari sering lupa dengan perkalian dasar yang telah di hapalkan; tidak bisa mengubahkan bentuk perkalian kedalam bentuk penjumlahan berulang; tidak dapat menentukan kalimat yang diketahui dan kalimat yang ditanya dalam soal cerita; tidak bisa menyelesaikan masalah operasi hitung perkalian secara mandiri karena masih menbutuhkan bantuan orang lain. Faktor yang mempengaruhi kesulitan yang dialami siswa yaitu; tidak paham konsep perkalian; menggunakan metode hapalam dalam memperlajari operasi hitung perkalian. Kata Kunci: Pemahaman Konsep Perkalian, Operasi hitung